2020
DOI: 10.1292/jvms.20-0167
|View full text |Cite
|
Sign up to set email alerts
|

Optimal activation methods for maximizing the concentrations of platelet-derived growth factor-BB and transforming growth factor-β1 in equine platelet-rich plasma

Abstract: Platelet-rich plasma (PRP) therapy has been widely applied in various medical fields including humans and horses. This study aimed to establish an optimal activation method to stably and reproducibly maximize the concentrations of platelet-derived growth factor-BB (PDGF-BB) and transforming growth factor-β1 (TGF-β1) contained in equine PRP. Autologous PRP was prepared from 11 Thoroughbreds. For the activation test, PRP was activated by either a single freeze-thaw cycle ( Fr ) or adding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…However, for bacterial flow cytometric analyzes in our study, these two solutions were found to be insufficient to lyse platelets. It was aimed to apply a platelet lysis method that can be easily used in every laboratory (Fukuda et al 2020 ; Rodrigues et al 2022 ; Kandoi et al 2018 ). In our literature review, it was seen that there were a few studies using the freeze-thaw method to achieve platelet lysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, for bacterial flow cytometric analyzes in our study, these two solutions were found to be insufficient to lyse platelets. It was aimed to apply a platelet lysis method that can be easily used in every laboratory (Fukuda et al 2020 ; Rodrigues et al 2022 ; Kandoi et al 2018 ). In our literature review, it was seen that there were a few studies using the freeze-thaw method to achieve platelet lysis.…”
Section: Methodsmentioning
confidence: 99%
“…71 Double freeze-and-thaw cycles have been suggested to be the optimal external activation method. 72 As for in vivo studies, there is no compelling evidence indicating whether activation is necessary. In the current review, six in vivo studies used platelet lysates and four studies used freeze-and-thaw cycles to activate platelet isolates.…”
Section: Summary Of In Vivo Studiesmentioning
confidence: 99%